2013
DOI: 10.1139/cjpp-2012-0250
|View full text |Cite
|
Sign up to set email alerts
|

Role of epidermal growth factor receptor transactivation in endothelin-1-induced enhanced expression of Gi protein and proliferation in A10 vascular smooth muscle cells

Abstract: We have recently shown that vasoactive peptides such as angiotensin II (Ang II) and endothelin-1 (ET-1) increase the expression of Gi proteins and the proliferation of A10 vascular smooth muscle cells (VSMC) through mitogen-activated protein (MAP) kinase-phosphoinositide (PI) 3-kinase pathways. This study was intended to examine the implication of epidermal growth factor receptor (EGFR) activation in ET-1-induced enhanced expression of Gi proteins and proliferation of A10 VSMC, and to further investigate the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…These results are consistent with our earlier studies showing a role of growth factor receptors in the enhanced expression of Gi␣ proteins and hyperproliferation of VSMCs from SHRs (17,33). In addition, ET-1 was also shown to enhance the expression of Gi␣ proteins and proliferation through the transactivation of EGFR in A 10 VSMC (18). Furthermore, a role of growth factor receptors in VSMC hypertrophy has also been shown by several studies (7,9,10).…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with our earlier studies showing a role of growth factor receptors in the enhanced expression of Gi␣ proteins and hyperproliferation of VSMCs from SHRs (17,33). In addition, ET-1 was also shown to enhance the expression of Gi␣ proteins and proliferation through the transactivation of EGFR in A 10 VSMC (18). Furthermore, a role of growth factor receptors in VSMC hypertrophy has also been shown by several studies (7,9,10).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we report for the first time that Sirt1 is overexpressed in aorta and VSMC from SHR and the enhanced expression of Sirt1 in VSMC from SHR contributes to the overexpression of Giα proteins that was shown to be implicated in the pathogenesis of hypertension and vascular remodeling [1,6,36,41]. The role of Sirt1 in Ang II-induced hypertension has been demonstrated in a recent study showing that Ang II-induced high blood pressure in wild type mice was significantly attenuated in Sirt1 knockout mice [28], however, these investigators did not examine if the attenuation of hypertension in Sirt1 knockout mice is attributed to the inhibition of Ang II-induced overexpression of Giα proteins.…”
Section: Discussionmentioning
confidence: 72%
“…The first study describing GPCR mediated transactivation of a PTKR was observed in rat fibroblasts where agonists to endothelin, thrombin and lysophosphatidic acid (LPA) receptor activated the EGFR (Daub et al 1996). Since this primary observation these GPCR agonists have been involved in transactivation of the EGFR in multiple cell models including vascular smooth muscle cells (VSMCs) Burch et al 2010aBurch et al , 2013Kamato et al 2016a;Gomez Sandoval et al 2013), cancer cells (Moody et al 2016;Tveteraas et al 2016) and brain injury model. Since the initial discovery, there have been almost two hundred reports of GPCR transactivation of PTKRs.…”
Section: Gpcr Transactivation Of Protein Tyrosine Kinase Receptorsmentioning
confidence: 99%